Correlation of intraoperative blood pressure variability and postoperative delirium in elderly hip fracture surgery - Peng Yang; Yu Fan; Wanyun Tang (Scientific Reports)
Abstract This study investigates the relationship between intraoperative blood pressure variability (BPV) and postoperative delirium (POD) after hip fracture surgery in geriatric patients. A retrospective analysis was conducted on 1002 geriatric patients who underwent hip fracture surgery. Intraoperative BPV was mainly quantified using the coefficient of variation in mean arterial pressure (CV-MAP). Patients were stratified into two groups (CV-MAP ≤ 10% vs. > 10%). Propensity score matching (PSM) balanced baseline characteristics. Multivariable logistic regression evaluated the association between CV-MAP and POD. Restricted cubic spline (RCS) analysis examined dose–response relationships. Subgroup analyses and interaction tests were conducted to examine effect modifications. POD occurred in 198 patients (19.8%). Patients with CV-MAP > 10% showed a significantly higher occurrence of POD than those with CV-MAP ≤ 10%, both before (24.6% vs. 16.4%, p < 0.001) and after PSM (25.2% vs. 18.9%, p = 0.032). Adjusted logistic regression confirmed CV-MAP > 10% as an independent predictor of POD (adjusted OR: 1.45, 95% CI 1.03–2.03, p = 0.033). RCS analysis revealed a nonlinear positive association between CV-MAP and POD risk. Subgroup analyses identified significant interactions between CV-MAP and variables such as age and ASA classification (p < 0.05). Elevated intraoperative BPV is independently associated with an increased risk of POD in elderly hip fracture patients, with nonlinear effects and potential modifiers. These findings underscore the importance of individualized blood pressure management to mitigate POD risk.